(untitled) (Journal of EAHIL, 2024)
A pilot project for a new current awareness service (CAS) aimed at community-based health care professionals in Ireland was launched in 2023. The CAS took the form of quarterly research bulletins for staff across six specialities: Diabetes Care, Nursing in the Community, Occupational Therapy, Palliative Care, Physiotherapy, and Speech and Language Therapy. The CAS was formally evaluated after 12 months to determine its usefulness to recipients and to consider it as a solution to scale nationally across all geographical areas in the Health Service Executive (HSE). Results indicate that community-based healthcare professionals are appreciative of bespoke discipline-focused research bulletins to keep them up-to-date with research and developments. The inclusion of HSE Library news and updates was also well received.